Predictive factors of first-year mortality in newly diagnosed end-stage renal disease patients commencing on hemodialysis in Kelantan - Lin, Ingrid Ting Pao (2018)
BACKGROUND: Globally the number of End-stage renal disease (ESRD) patients has been increasing in trend both developed and developing countries, worldwide. The annual death rate for ESRD on hemodialysis (HD) in Malaysia 2015 was 13.8%. The overall 5 years and 10 years survival on dialysis were 52% and 27% respectively. The trend for death rate among HD patients had gradually increased over the past 2 decades. Dialysis has a massive impact on financial resources and utilization. The highest incidence of mortality is found to be during the first year of initiation of hemodialysis. Several studies have comprehensively analyzed various existing risk factors during the pre-dialysis stage associated with first-year mortality after commencing HD; however, the results were inconsistent due to lack of local data. This study was carried out to identify prognostic factors that contribute to the first-year mortality in newly diagnosed ESRD patients in the state of Kelantan, Malaysia. METHOD: A prospective cohort study was conducted involving 373 ESRD patients newly initiated hemodialysis from 28 hemodialysis center in Kelantan from 1st January 2016 to 31st December 2016. Follow up of one year after recruitment of the subjects was done until 31st December 2017. All patients who fulfilled the criteria were included in the study. The required information on variables of interest was taken every 3 months during blood taking and recorded in ADNAN (Advanced Dialysis Nephrology Application) system. The survival status until 31st December 2017 was recorded into a data collection form.RESULTS: The overall cumulative survival of ESRD during the first-year initiation on HD in Kelantan was 89.5 (95% CI 86.5, 92.7) percent. Based on Cox Proportional Hazards Regression multivariable analysis after adjusting other variables, the significant prognostic factors that influenced the risk of mortality in ESRD patients during first-year of initiation of hemodialysis were female gender (HR=2.40, 95% CI: 1.23, 4.69) and serum albumin less than 30 g/l (HR=0.93, 95% CI: 0.89, 0.98). CONCLUSION: The survival rate of ESRD patients during the first-year initiation of HD in Kelantan was comparable with other developed countries. Significant independent prognostic factors identified were considered similar to other countries.